'Here comes the story of the Hurricane': a case report of AL cardiac amyloidosis and myocardial bridging. Issue 7 (31st May 2022) - Cappannoli, Luigi; Ciliberti, Giuseppe; Restivo, Attilio; Palumbo, Pierpaolo; D'Alò, Francesco; Sanna, Tommaso; Crea, Filippo; D'Amario, Domenico
Abstract: Background: Cardiac amyloidosis (CA) is a rapidly progressive infiltrative cardiomyopathy, whose role is emerging as a not-so-rare disorder leading to heart failure (HF). Myocardial bridge (MB) is the most common inborn coronary artery variant, and its clinical relevance is still matter of debate. The exceptional coexistence of these two conditions could accelerate disease progression and worsen the already compromised clinical conditions. Case summary: We present the case of a 76-year-old female patient experiencing relapsing HF decompensation and presenting to our centre with dyspnoea at rest and severe peripheral congestion. Echocardiogram showed severe concentric hypertrophy, severe biventricular contractile dysfunction, and third-degree diastolic dysfunction. Coronary angiography excluded epicardial atherosclerotic disease, though displaying a long intramyocardial course of left anterior descending artery. Physiological invasive test was achieved in terms of instantaneous wave-free ratio (iFR), both at baseline and after inotropic and chronotropic stimuli, and attested haemodynamic significance. Concurrently, the diagnostic flow chart for CA was accomplished, by means of both invasive (periumbilical fat biopsy, bone marrow aspiration) and non-invasive tests ( 99m Tc-diphosphonate scintigraphy, serum-urine immunofixation) that confirmed the suspect of primary amyloidosis. Acute HF therapy was personalized according to the singularity of the case, avoiding both nitrates and beta-blockers, then first cycle of chemotherapy was started. Discussion: Our clinical case shows a unique interaction between infiltrative cardiomyopathy and coronary artery abnormality. Amyloidosis can contribute to the ischaemic burden of the MB and this may, in turn, abbreviate the path to HF decompensation.